DETERMINANTS OF CASH HOLDING OF NON-CYCLICALS SECTOR COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Angelika, Shery; Bangun, Nurainun; Lukman, Hendro (International Journal of Application on Economics and Business, 2023)
The Indonesian government’s response to COVID-19 involving social restrictions has led to a slowdown and limitations in economic activities. Cash holding can act as a safeguard and play a crucial part in companies, particularly in covering transaction activities and operational expenses. On the other hand, holding an excessive amount of cash also has disadvantages, as it can lead to missed profit opportunities since idle cash does not generate income. This study aims to analyze the impact of liquidity, net working capital, and growth opportunity on cash holding of consumer non-cyclicals companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. The data used in this study is secondary data collected from the company’s financial reports from the IDX website (www.idx.co.id). The sample selection in this study was carried out through purposive sampling, resulting in a total of 115 data included in the research sample. The data was proceeded and analyzed using Microsoft Excel 2019 and Eviews 13. This study uses the panel data analysis method with a random-effect model as the estimation model and multiple linear regression analysis. The research was continued by testing classical assumptions, F-test, T-test, and coefficient of determination test. The results show that liquidity and net working capital have a positive and significant effect on cash holding, while growth opportunity does not affect cash holding. Management of non-cyclical consumer companies must pay more attention to liquidity and net working capital to maintain cash holdings. The implications of this research show the importance of maintaining liquidity and working capital rather than paying attention to company growth opportunities, because growth will be easily achieved if you have adequate cash holdings.